QUANTITATIVE STRUCTURE-ACTIVITY RELATIONSHIP (QSAR) STUDY OF EUGENOL DERIVATIVES AS ANTIOXIDANT COMPOUNDS (Proceedings of the International Conference on Food, Nutrition, Health and Lifestyle, 2022)
Non-Communicable Diseases (NCDs) are one of the main problems in the health sector. This problem is shown by 70% of the world's deaths caused by NCDs. One way to overcome this is with Eugenol which is an antioxidant, indicated by an IC50 value of 4,38 μg/mL. The development of derivatives of eugenol compounds resulted in lower antioxidant activity values than eugenol activity. A study of the Quantitative Structure and Activity Relationship (QSAR) was carrying out on eugenol derivative compounds with antioxidant activity. This study aims to analyze the QSAR of eugenol-derived compounds and determine the computational model of the QSAR equation for eugenol-derived compounds. The data used are 21 data on eugenol-derived compounds that have been tested for their antioxidant activity using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical experimentally (in vitro) from various literature. The data calculates computationally using the Hartree Fock (HF) calculation with a basis set of 6-311G. The computational results obtained are then analyzed using the multilinear regression method. The results of the QSAR analysis showed that the linear correlation coefficient (R) was 0,973, which means the predictive activity value was close to the experimental activity value. The best QSAR equation model obtained was compiled by an electronic descriptor with the energy parameter HOMO and the energy difference HOMO-LUMO (Gap), a hydrophobic descriptor with a log P parameter, and a steric descriptor with a Balaban index, with the equation model:Log IC50 = 6,442 + (26,257) HOMO + (9,231) GAP + (0,056) LOGP – (0,433) BALABAN
Keywords: QSAR; Eugenol; Antioxidants; Hartree Fock; 6-311G